Expression of IL-18, IL-18 Binding Protein, and IL-18 Receptor by Normal and Cancerous Human Ovarian Tissues: Possible Implication of IL-18 in the Pathogenesis of Ovarian Carcinoma - Liat Medina; Alex Rabinovich; Benjamin Piura; Victor Dyomin; Ruthy Shaco Levy; Mahmoud Huleihel (Mediators of Inflammation)
Proinflammatory cytokine IL-18 has been shown to be elevated in the sera of ovarian carcinoma patients. The aim of the study was to examine the levels and cellular origin of IL-18, IL-18 binding protein, and IL-18 receptor in normal and cancerous ovarian tissues. Ovarian tissue samples were examined by immunohistochemical staining for IL-18, IL-18BP, and IL-18R and mRNA of these cytokines was analyzed with semiquantitative PT-PCR. IL-18 levels were significantly higher in cancerous ovarian tissues (P=0.0007), IL-18BP levels were significantly higher in normal ovarian tissues (P=0.04), and the ratio of IL-18/IL-18BP was significantly higher in cancerous ovarian tissues (P=0.036). Cancerous ovarian tissues expressed significantly higher IL-18 mRNA levels (P=0.025), while there was no difference in the expression of IL-18BP mRNA and IL-18R mRNA between cancerous and normal ovarian tissues. IL-18 and IL-18BP were expressed dominantly in the epithelial cells of both cancerous and normal ovarian tissues, while IL-18R was expressed dominantly in the epithelial cells of cancerous ovarian tissues but expressed similarly in the epithelial and stromal cells of normal cancerous tissues. This study indicates a possible role of IL-18, IL-18BP, and IL-18R in the pathogenesis of epithelial ovarian carcinoma.